The role of glycosylation and sequence variation in the regulation of von Willebrand Factor plasma levels - Rawley, Orla. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2014)
Von Willebrand Factor (VWF) is a multimeric plasma sialoglycoprotein that plays an important role in primary haemostasis by mediating platelet capture at sites of vascular injury. In the normal population, VWF plasma concentrations vary over a wide range (5-20μg/mL). Importantly, VWF glycosylation, and single amino acid substitutions in the VWF molecule, have both been shown to contribute to variation in plasma VWF levels by regulating VWF clearance. However the biological mechanism(s) involved have not been defined.
Keywords: Haematology, Ph.D.; Ph.D. Trinity College Dublin